Docencia y docentes de diseño arquitectónico (2011)
As part of developing a research process, focusing on teaching and learning of architecture, this article includes some reflections on the work of teachers in Architectural Design, this discipline which constitutes the core of architectural education based on the premise that those engaged in this work generally do not have sufficient pedagogical training for adequate performance, but truly appreciate and love of teaching and learning environment. We reflect here on some personality traits of the architect in general, then try to understand certain profiles of those involved in teaching design, characterizing his work from some of its human attitudes, pedagogical and psychological, without going deeper into them, but having seen them as mere external manifestations of certain “styles” that have been encrusted with tradition in design education, also called “architectural design studio.”